(untitled) (World Bulletin of Social Sciences, 2024)
The article talks about improving students’ competence through media. Currently, the problem of forming competencies in requirements is attracting great interest among scientists and young researchers. Thus, "in the formation of competencies of the future specialist, they rely not on the availability of scientific knowledge, but on the ability to solve production problems and perform production activities within the framework of the standard